2013
DOI: 10.1063/1.4793412
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic influence on the martensitic transformation entropy in Ni-Mn-In metamagnetic alloy

Abstract: We study the martensitic transformation (MT) of metamagnetic shape memory alloy Ni50Mn34.5In15.5 in the magnetic fields up to 12 T. The observed dependence of the MT temperature, Tm, on the field is highly nonlinear. As far as magnetization change, ΔM, remains field-independent, a depart from linearity of Tm(H) function is attributed to a decrease of the transformation entropy, ΔS. This decrease correlates with the parameter (TC-Tm), controlled by magnetic field, where TC is the Curie temperature of austenite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 15 publications
5
43
0
Order By: Relevance
“…9, we know that the entropy change Ds at M s decreases as M s decreases. Therefore, Ds at M s comes to decrease with increasing magnetic field, as reported by Barandiaran et al [23] for a Ni 50 Mn 34.5 In 15.5 alloy. Concerning the dependence of Ds on the temperature, Umetsu et al [24] reported that the sign of Ds changes at $80 K for a Ni 50 Mn 34 In 16 alloy, and they interpreted that such an anomalous behavior in Ds is responsible for the kinetic arrest of MT in that system.…”
Section: Evaluation Of the Difference In Free Energy And Equilibrium supporting
confidence: 58%
“…9, we know that the entropy change Ds at M s decreases as M s decreases. Therefore, Ds at M s comes to decrease with increasing magnetic field, as reported by Barandiaran et al [23] for a Ni 50 Mn 34.5 In 15.5 alloy. Concerning the dependence of Ds on the temperature, Umetsu et al [24] reported that the sign of Ds changes at $80 K for a Ni 50 Mn 34 In 16 alloy, and they interpreted that such an anomalous behavior in Ds is responsible for the kinetic arrest of MT in that system.…”
Section: Evaluation Of the Difference In Free Energy And Equilibrium supporting
confidence: 58%
“…T T − to S Δ was verified very recently in the experiments with Ni-Mn-In alloys (see Figure 15) [96]. Figure 15.…”
Section: Mf Msmentioning
confidence: 77%
“…Figure 15. The experimental verification of the inverse proportionality of two-phase temperature interval to entropy change [96]. The dashed line presents a linear fit to the experimental points.…”
Section: Mf Msmentioning
confidence: 99%
“…However, due to the large magnetic anisotropy in Ni-Mn-Ga alloys [2,91], a low magnetic field results in a small decrease of T M s [88,89]. Nevertheless, for Ni-Mn-In alloys, the magnetization of the parent phase is much greater than that of martensite phase, and thus magnetic fields will effectively decrease the T M s [23,[92][93][94][95][96], as is schematically shown in Fig. 2.3(c).…”
Section: Clausius-clapeyron Equationsmentioning
confidence: 99%